3D-printed multisampling holder for microcomputed tomography applied to life and materials science research. (November 2021) - Vasconcelos, Isabel; Franco, Margarida; Pereira, Mário; Duarte, Isabel; Ginjeira, António; Alves, Nuno
Highlights: Micro-CT is a gold standard method applied in life and material science. The classic solutions of sampling mounting show some limitations. The 3D printing process enables the fabrication of a holder, which exactly fits the experimental setup. A multisampling holder allows to do multi-analysis from the same scan, reducing the scan duration time, cost and data storage. Abstract: The aim of this work was to design, fabricate, test and validate a 3D-printed multisampling holder for multi-analysis by microcomputed tomography. Different raw materials were scanned by microcomputed tomography. The raw material chosen was used to fabricate the holder by 3D printing. To validate the multisampling holder, five teeth were filled with a high density-material and scanned in two ways: a single and a multisampling scan mode. For each tooth, the root canal filling volume, porosity volume, closed pore volume, and open pore volume were calculated and compared when the same tooth was scanned in the two sampling scan mode. ABSplus P430™ allowed a high transmission value (84.3 %), and then it was the polymeric material selected to fabricate the holder. In a single sampling scan mode, the scan duration for scanning five teeth was 87.42 min, contrasting with 21.51 min for a multisampling scan mode, which scanned five teeth at the same time. The scan duration time and the cost using a multisampling holder represented a reduction of 75 % and the data volume generated represented a reduction of 60 %. Comparing the two scan modes, the results also showed that the difference of root canal filling volume, porosity volume, closed pore volume, and open pore volume was not statistically significant (p > .05). The multisampling holder was validated to do multi-analysis by microcomputed tomography without significant loss of quantitative accuracy data, allowing a reduction in scan duration time, imaging cost, and data storage.